Chemoradiotherapy With Generic Cisplatin Formulations for Head and Neck Cancers. (27th January 2018) - Shimada, Rie; Tsukahara, Kiyoaki; Takase, Soichiro; Okamoto, Isaku; Sato, Hiroki; Katsube, Yasuaki; Maruyama, Ryo; Shimizu, Akira
The use of generic drugs has been increasing. However, studies of the safety of generic cisplatin (CDDP) for the treatment of head and neck cancer (HNC) have not been reported. This study investigated the treatment completion rates and incidence of CDDP-related adverse events in patients with advanced HNC treated with concurrent chemoradiotherapy (CRT) using generic CDDP. This study included 72 patients who received concurrent CRT using generic CDDP. The number of courses of CDDP was 3 in 45 patients, 2 in 19 patients, and 1 in 8 patients. During 154 courses of 80 mg/m 2 generic CDDP, grade 3/4 leukopenia in 21 (14%), neutropenia in 18 (12%), and hypochromia in 8 (5%) cases were reported. Grade 2 elevated serum creatinine occurred in 4 cases (3%), but no grade 3/4 elevated serum creatinine was reported. These results suggest that CRT using generic CDDP is well tolerated in patients with HNC.